TINDAK ILOKUSI DALAM FILM DIVERGENT SERIES INSURGENT KARYA ROBERT SCHWENTKE (SUATU ANALISIS PRAGMATIK) - Rembe, Paskalis K.; Jansen, Frieda Th.; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTSThis research entitled â€œ Illocutionary Act in the Film Divergent Series â€œInsurgentâ€Â ByÂ Robert Schwentke : A Pragmatic Analysisâ€, is an analysis of pragmatic investigation that focus on one aspect of speech acts called illocutionary act. This researchÂ is an attempt to find out the kinds and funtions of illocutionary act in theÂ film. The data have been taken from the characters utterances in the film. The writer analyzed the data descriptively by concentrating on utterance which contain illocution. The theory used in this reseach is taken from Austin theory aboutÂ illocutionary acts. The findings of this research show that the kinds and functions of the illocutionary act found in the film Divergent series â€œInsurgentâ€ is classified into five categories, those are Verdictives: (acquit), (convict), (find as a matter of fact), (hold as a matter of fact), (interpret as), (understand), (read it as), (rule), (calculate), (reckon), (estimate), (locate), (place), (date), (measure), (value), and (describe). Exercitives :Â (appointing), (choose),Â (ordering), (voting),Â (urging),Â (advising), (warning), (name), (proclaim), and (direct). Commistives : (promise), (undertake), (contract),Â (swear),Â (agree), (declare for),Â (oppose), (to be on), andÂ (espouse). Behabitives: (congratulating), (challenging), (apologizing), (cursing), and (condoling). Expositive: giving a view, giving an explanation or opinion, giving an explanation of uses and references.Â Keywords: Illocutionary act, film Divergent Series Insurgent, pragmatics analysis.